The role of adverse childhood experiences and attachment styles in social anxiety disorder in adolescents. (July 2022) - Derin, Songul; Selman, Saliha B.; Alyanak, Behiye; Soylu, Nusret
Background: Social Anxiety Disorder (SAD) is one of the most common disorders of adolescence and results in marked impairments in social and academic/occupational activities that likely to persist into adulthood. Multiple etiological factors contribute to the development of social anxiety disorder. Two critical factors in presenting with a primary diagnosis of SAD might be adverse childhood experiences (ACEs) and attachment styles. The current study examined how ACEs and attachment styles may be related to SAD in adolescents. Methods: 60 participants with ages ranging from 11 to 18 (M = 14.6; female = 36), who have a primary diagnosis of SAD and 60 control group adolescents (M = 14.6; female = 30) were included in the study. Both groups completed the Liebowitz Social Anxiety Scale (LSAS), the Childhood Trauma Questionnaire (CTQ), and the Adolescent Relationship Scales Questionnaire (A-RSQ). Results: After controlling adolescent gender and parental education levels, childhood emotional neglect and income significantly predicted an increased risk for adolescents' SAD diagnosis. Attachment styles did not significantly contribute to predicting adolescents' SAD diagnosis after controlling childhood emotional neglect. Conclusion: The high predictive value of emotional neglect in childhood emphasizes its importance as a risk factor of SAD in adolescence.